2015
DOI: 10.4102/jsava.v86i1.1286
|View full text |Cite
|
Sign up to set email alerts
|

Suspected lead poisoning in two captive cheetahs (<i>Acinonyx jubatus jubatus</i>) in South Africa, in 2008 and 2013

Abstract: Whilst lead poisoning in raptors, scavenging birds and waterfowl is well studied and common knowledge, there is surprisingly little literature detailing the risk to mammalian scavengers and captive carnivores fed hunted meat. This case report describes the death of two captive cheetahs (Acinonyx jubatus jubatus) following acute onset of nervous symptoms. Clinical signs included hyper-excitability, seizures, arched back, tail held abnormally high and hyper-salivation. Necropsy findings included bullets or a bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…The consumption of Pb-contaminated meat usually produces cumulative effects on consumers [12]. The edible offal and muscle Pb concentration was higher than the permissible limits of 0.1 mg/kg for muscle meat and 0.5 mg/Kg for offal as set by WHO, FAO, and E.O.S [20][21] in the present study. The similar findings of higher Pb concentrations were also observed by other researchers [22][23][24] in edible offal and muscles of sheep and other food animals.…”
Section: Resultscontrasting
confidence: 54%
“…The consumption of Pb-contaminated meat usually produces cumulative effects on consumers [12]. The edible offal and muscle Pb concentration was higher than the permissible limits of 0.1 mg/kg for muscle meat and 0.5 mg/Kg for offal as set by WHO, FAO, and E.O.S [20][21] in the present study. The similar findings of higher Pb concentrations were also observed by other researchers [22][23][24] in edible offal and muscles of sheep and other food animals.…”
Section: Resultscontrasting
confidence: 54%
“…2 Ingestion of unclaimed shot animals, body parts discarded by hunters and bullet/wound channel, which is the penetrating wound inflicted by the bullet, are the most likely causes of high lead concentrations in wildlife. 2,3 Two cases of suspected lead toxicosis were reported in captive cheetahs (Acinonyx jubatus jubatus) at a rehabilitation and breeding program in South Africa, with food given to the cheetahs (i.e. shot antelopes, birds, feral donkeys and horses) suspected to contain whole bullets or fragments.…”
Section: Methodsmentioning
confidence: 99%
“…shot antelopes, birds, feral donkeys and horses) suspected to contain whole bullets or fragments. 3 A later study showed that feeding hunting dogs the trimmings of lead-shot game might present a risk of lead intoxication, and recommended not feeding domestic or wild animals with trimmings close to the wound channel. 4 Clinical lead toxicosis can result in neurological signs (dullness, muscular tremors, ataxia, convulsions and coma), anaemia, renal dysfunction including Fanconi's syndrome and impaired bone mineralisation and healing with increased risk of fracture in both birds and mammals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations